Qualitative analysis of patients’ feedback from a PROMs survey of cancer patients in England - Richard Wagland; Jessica Corner; Adam Glaser; Sir Mike Richards (BMJ Open)
Objective This study examined how free-text comments from cancer survivors could complement formal patient-reported outcome measures (PROMs), as part of the England PROMs survey programme for cancer.Design A qualitative content analysis was conducted of responses to a single open-ended free-text question placed at the end of the cross-sectional population-based postal questionnaire.Setting Individuals were identified through three UK Cancer Registries and questionnaires were posted to their home addresses.Participants A random sample of individuals (n=4992) diagnosed with breast, colorectal, non-Hodgkins lymphoma or prostate cancer at 1, 2, 3 and 5 years earlier.Results 3300 participants completed the survey (68% response rate). Of these 1056 (32%) completed the free-text comments box, indicating a high level of commitment to provide written feedback on patient experience. Almost a fifth (19%) related experiences of excellent care during the treatment phase, with only 8% reporting negative experiences. This contrasted with experiences of care after primary cancer treatment where the majority were negative. Factors impacting negatively upon patient-reported outcomes included the emotional impact of cancer; poor experiences of treatment and care; comorbidities, treatment side effects, social difficulties and inadequate preparation for a wide range of sometimes long-lasting on-going physical and psychological problems. Mediating factors assisting recovery incorporated both professional-led factors, such as quality of preparation for anticipated problems and aftercare services, and participant-led factors, such as learning from other cancer survivors and self-learning through trial and error. The support of friends and family was also a factor in participants' outcomes.Conclusions This analysis of free-text comments complements quantitative analysis of PROMs measure's by illuminating relationships between factors that impact on quality of life (QoL) and indicate why cancer patients may experience significantly worse QoL than the general population. The data suggest more systematic preparation and aftercare for individuals to self-manage post-treatment problems might improve QoL outcomes among cancer survivors.